Polarizing plate and display device using same
By using the protective films A and B with specific moisture permeability and composition on the polarizer, the deterioration problem caused by moisture retention in high temperature and high humidity environments is solved, and the thin, high bending and durability are achieved, which is suitable for vehicle-mounted display devices.
Patent Information
- Application Number
- CN202380029038.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-16
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing polarizer has poor durability in high temperature and high humidity environments, especially the high water vapor barrier properties of the protective film, which lead to deterioration caused by moisture retention, and it is difficult to achieve thinning and high bending properties in curved surface areas.
The protective film A and the protective film B are pasted on one side of the polarizing plate. The protective film A is made of a hard coat layer composed of a (meth)acrylate compound and a composition containing an alicyclic structure, and the moisture permeability is 240 g/ The protective film B is composed of cycloolefin polymers or the like, with a moisture permeability of 70 g/m2/day or more, and the thickness of the two is controlled to be less than 50 μm and 10 to 100 μm respectively.
It realizes durability and high bending properties in high temperature and high humidity environments, suppresses moisture retention, extends the optical performance life of the polarizer, and is suitable for on-board display devices in curved surface areas.
Smart Images

Figure CN119173793A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate and a display device using the polarizing plate. Background Art
[0002] Polyvinyl alcohol (PVA) is mainly used in polarizing plates used in display devices. PVA has extremely poor water resistance, so protective films are attached to both sides. In the past, protective films for polarizing plates used triacetyl cellulose (TAC) films laminated with a hard coating layer, with a moisture permeability of 300 to 1000 g / m 2 / day or so, but there is a problem that under the severe conditions of high temperature and high humidity, it is impossible to prevent PVA from absorbing water and causing degradation.
[0003] Therefore, the development of protective films using cycloolefin polymer (COP) and polyethylene terephthalate (PET) instead of TAC has been carried out, and the moisture permeability of the protective film can be reduced to 5 to 100 g / m 2 / day or so.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-144076 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In recent years, polarizing plates with durability under extremely high temperature and humidity have been required for automotive applications, etc. In high temperature and humidity environments, when the water vapor barrier property of the protective film is too high, although there is no moisture intrusion from the outside, there are cases where moisture generated from the substrate or the adhesive used to attach the protective film stays in the polarizing plate and causes deterioration.
[0009] In addition, as the area of vehicle-mounted displays increases, the applications of displays also expand, and displays are used not only on flat surfaces but also on curved surfaces. Under such circumstances, a polarizing plate with reduced thickness and high bendability is required.
[0010] Therefore, an object of the present invention is to provide a polarizing plate which is thin and highly flexible and has durability in a high-temperature and high-humidity environment, and a display device using the polarizing plate.
[0011] Means for solving problems
[0012] The polarizing plate of the present invention is a polarizing plate in which a protective film A is attached to one surface of a polarizer and a protective film B is attached to the other surface, characterized in that the moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B at 40°C and 90%RH simultaneously satisfy the following conditions (1) and (2), the protective film A has a hard coating layer composed of a cured film of a composition, the composition contains a (meth)acrylate compound (A), a (meth)acrylate compound (B) containing an alicyclic structure, and a photopolymerization initiator (C), and the content ratio of the (meth)acrylate compound (B) is 20% by mass or more of the total solid content, and the thickness of the protective film A is less than 50 μm.
[0013] 240g / m 2 / day>TA>70g / m 2 / day…(1)
[0014] 70g / m 2 / day≥TB…(2).
[0015] Furthermore, a display device according to the present invention includes the above-mentioned polarizing plate.
[0016] Effects of the Invention
[0017] According to the present invention, it is possible to provide a polarizing plate which is thin and highly flexible and has durability in a high-temperature and high-humidity environment, and a display device using the polarizing plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] [ Figure 1 ] Figure 1 It is a cross-sectional view showing a schematic structure of a polarizing plate according to an embodiment. DETAILED DESCRIPTION
[0019] The polarizing plate 10 includes a polarizer 1, a protective film A attached to one side of the polarizer 1, and a protective film B attached to the other side of the polarizer 1. The polarizer 1 is formed by adsorbing iodine or a dye on a polyvinyl alcohol (PVA) film and orienting it. Since the PVA constituting the polarizer 1 has poor strength and water resistance, the protective films A and B are attached to both sides of the polarizer 1.
[0020] The protective film A is a hard coating film in which a hard coating layer 3 is laminated on one surface of a TAC film 2. The hard coating layer 3 is a functional layer that covers the soft TAC film 2 and imparts hardness to the protective film A.
[0021] The hard coating layer 3 can be formed by coating a composition containing a (meth)acrylate compound containing an alicyclic structure and a photopolymerization initiator on one surface of the TAC film 2, drying the composition, and curing the coating film by ultraviolet irradiation. It should be noted that in this specification, "(meth)acrylate" is a general term for both acrylate and methacrylate, and "(meth)acryloyl" is a general term for both acryloyl and methacryloyl.
[0022] The (meth)acrylate containing an alicyclic structure can improve the hydrophobicity of the hard coating layer 3, impart water vapor barrier properties to the protective film A, and improve the bending resistance of the hard coating layer 3. The (meth)acrylate containing an alicyclic structure is not particularly limited, and for example, (meth)acrylates having one or more of a cyclopentane structure, a dicyclopentane structure, a cyclohexane structure, a cyclodecane structure, a tricyclodecane structure, an isobornyl structure, and an adamantane structure can be used.
[0023] Specific examples of the (meth)acrylate containing an alicyclic structure include: monofunctional (meth)acrylates such as cyclohexyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexanol (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, 2-dicyclopentenyloxyethyl (meth)acrylate, dicyclopentenyloxyethyl methacrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecyl (meth)acrylate, tricyclodecane dimethanol mono(meth)acrylate, and adamantyl (meth)acrylate; and cyclohexanedimethanol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, di(meth)acrylate, and isobornyl (meth)acrylate. Polyfunctional (meth)acrylates such as dicyclopentenyl meth)acrylate, dicyclopentadienyl di(meth)acrylate, bornyl di(meth)acrylate, isobornyl di(meth)acrylate, tricyclodecyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, adamantyl di(meth)acrylate, adamantane dimethanol di(meth)acrylate, adamantane diethanol di(meth)acrylate, dihydroxymethyl dicyclopentane di(meth)acrylate, norbornane dimethylol di(meth)acrylate, cyclohexanedimethanol tri(meth)acrylate, adamantyl tri(meth)acrylate, adamantane trimethanol tri(meth)acrylate, norbornane trimethylol tri(meth)acrylate, tricyclodecane trimethanol tri(meth)acrylate, and perhydro-1,4,5,8-dimethylnaphthalene-2,3,7-(oxymethyl) tri(meth)acrylate. These (meth)acrylates may be used alone or as a mixture of one or more thereof.
[0024] The proportion of the (meth)acrylate containing an alicyclic structure is preferably set to 20% by mass or more of the total solid content of the hard coat layer forming composition. When the proportion of the (meth)acrylate containing an alicyclic structure is 20% by mass or more of the total solid content, the moisture permeability of the protective film A can be within the range described below, thereby improving the bending resistance of the hard coat layer 3. The upper limit of the proportion of the (meth)acrylate containing an alicyclic structure is not particularly limited, but due to the addition of a photopolymerization initiator, it is 99% by mass or less of the total solid content.
[0025] In addition to the (meth)acrylate containing an alicyclic structure, other active energy ray-curable compounds may be used. As the active energy ray-curable compound, for example, a monofunctional, difunctional, or trifunctional or higher-functional (meth)acrylate monomer may be used.
[0026] Examples of the monofunctional (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, and (meth)acrylate. Isodecyl acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphoric acid (meth)acrylate, ethylene oxide modified phosphoric acid (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified phenoxy (meth)acrylate meth)acrylate, phenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogenated phthalate, 2-(meth)acryloyloxyethyl hydrogenated phthalate -(meth)acryloxypropyl ester, 2-(meth)acryloxypropyl hexahydrohydrophthalate, 2-(meth)acryloxypropyl tetrahydrohydrophthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, and adamantane derivative mono(meth)acrylate such as adamantane acrylate having a monovalent mono(meth)acrylate derived from 2-adamantane or adamantanediol.
[0027] Examples of the bifunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate and other di(meth)acrylates.
[0028] Examples of trifunctional or higher (meth)acrylates include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tri-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerol tri(meth)acrylate and the like; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate and the like; Acid ester compounds; polyfunctional (meth)acrylate compounds having three or more functions such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate; and polyfunctional (meth)acrylate compounds in which a part of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone, etc.
[0029] In addition, urethane (meth)acrylates may be used as the polyfunctional monomers. Examples of urethane (meth)acrylates include urethane (meth)acrylates obtained by reacting a product obtained by reacting an isocyanate monomer or prepolymer with a polyester polyol with a (meth)acrylate monomer having a hydroxyl group.
[0030] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.
[0031] The above-mentioned multifunctional monomer may be used alone or in combination of two or more. In addition, the above-mentioned multifunctional monomer may be a monomer in the composition or an oligomer obtained by partial polymerization.
[0032] As a polymerization initiator, a polymerization initiator that generates free radicals by ultraviolet irradiation can be used. As a polymerization initiator, free radical polymerization initiators such as acetophenone, benzophenone, thioxanthone, benzoin, benzoin methyl ether, and acylphosphine oxide can be used. As a polymerization initiator, for example, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, bis (2,4,6-trimethylbenzoyl) phenyl phosphine oxide, 2,2-diethoxy acetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-phenyl acetophenone, dibenzoyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, 2-chlorothioxanthone, etc. can be used alone. Among these, one kind can be used alone, or two or more kinds can be used in combination.
[0033] A solvent may be added to the hard coat forming composition as required. As the solvent, one of the following solvents may be used or a mixture of two or more thereof: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropanol, and isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as dimethyl carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone and dimethylformamide.
[0034] In addition, various additives such as antistatic agents, defoaming agents, antioxidants, ultraviolet absorbers, infrared absorbers, colorants, light stabilizers, inhibitors, photosensitizers, antifouling agents, leveling agents, oleophobic agents, hydrophobic agents, anti-fingerprint adhesion agents, etc. may be added to the hard coat forming composition as needed.
[0035] There is no particular limitation on the method for applying the hard coat-forming composition, and for example, coating can be performed using a spin coater, a roll coater, a reverse roll coater, a gravure coater, a micro gravure coater, an air knife coater, a rod coater, a wire bar coater, a die coater, a dip coater, a spray coater, an applicator, or the like.
[0036] The thickness (total thickness) of the protective film A is preferably less than 50 μm. When the polarizing plate 10 is bent with the hard coating layer 3 facing outward, stress is concentrated on the surface of the hard coating layer 3. When the thickness of the protective film A is 50 μm or more, cracks are easily generated in the hard coating layer 3 when the polarizing plate 10 is bent.
[0037] Moreover, the pencil hardness of the protective film A (hard coat film) is preferably 3 H or more. When the pencil hardness of the protective film A is 3 H or more, the surface hardness of the polarizing plate is good and the durability is improved.
[0038] The thickness of the TAC film 2 and the hard coating layer 3 used in the protective film A are not particularly limited as long as the thickness of the protective film A is 50 μm. As an example, the thickness of the TAC film 2 is 25 to 40 μm, and the thickness of the hard coating layer 3 is 5 to 10 μm.
[0039] The protective film B is a low moisture permeable film made of any one of cycloolefin polymer (COP), polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA). The protective film B is attached to the polarizer 1 via an ultraviolet curable adhesive, for example. The thickness of the protective film B is not particularly limited, but is preferably 10 to 100 μm.
[0040] In addition, in the display device, the protective film B is arranged on the display panel side, and the hard coat layer of the protective film A is arranged on the viewing side (the side opposite to the display panel).
[0041] The TAC film of the protective film A is pasted on the PVA film of the polarizer 1 using a water paste (PVA aqueous solution) as an adhesive. It should be noted that in order to ensure the close adhesion between the TAC film and the PVA film, the protective film A is subjected to a saponification treatment before pasting. Since a water paste is used when the protective film A is pasted on the polarizer 1, moisture may be contained in the adhesive layer and the TAC film even after the drying process. In the case where both the protective films A and B are composed of a film with low moisture permeability, although the intrusion of moisture from the outside can be suppressed, in an extremely high temperature environment such as in a car in summer, the moisture contained in the adhesive and / or the TAC film continues to remain in the polarizing plate 10, thereby causing the polarizer 1 to deteriorate.
[0042] Therefore, in the polarizing plate 10 involved in this embodiment, by setting a difference between the moisture permeability of the protective film A and the moisture permeability of the protective film B, and setting the moisture permeabilities of the protective film A and the protective film B within specific ranges, respectively, the deterioration of the polarizer 1 caused by moisture from the adhesive and / or TAC film is suppressed.
[0043] Specifically, when the moisture permeabilities of the protective films A and B at 40°C and 90%RH are TA and TB, respectively, TA and TB simultaneously satisfy the following conditions (1) and (2). It should be noted that both moisture permeabilities TA and TB are values measured according to the moisture permeability test method (cup method) for moisture-proof packaging materials specified in JIS Z 0208:1976.
[0044] 240g / m 2 / day>TA>70g / m2 / day…(1)
[0045] 70g / m 2 / day≥TB…(2)
[0046] The polarizing plate 10 involved in this embodiment can suppress the intrusion of moisture from the outside into the interior of the polarizing plate by simultaneously satisfying the above-mentioned conditions (1) and (2), and can discharge to the outside the moisture generated by the adhesive used to adhere the protective film A and the polarizer 1 and / or the TAC film of the protective film A when exposed to a high temperature environment of 85°C, for example.
[0047] As described above, the polarizing plate 10 involved in this embodiment has a protective film A and a protective film B that satisfy the above conditions (1) and (2). With this structure, the protective film B arranged on the display panel side almost blocks the entry and exit of moisture. On the other hand, the protective film A arranged on the viewing side can inhibit moisture from invading the inside of the polarizing plate 10 from the outside, and can release the moisture generated inside the polarizing plate 10 in an extremely high temperature environment. Therefore, in the polarizing plate 10 involved in this embodiment, when used in a high temperature environment, the moisture generated inside the polarizing plate 10 will not stay, so the degradation of the polarizer can be suppressed, thereby maintaining the optical performance of the polarizing plate 10 for a longer period of time.
[0048] In addition, since the thickness of the protective film A is less than 50 μm, the polarizing plate 10 can be made thinner, and cracks in the hard coat layer 3 can be suppressed when the polarizing plate 10 is bent, thereby improving the bending resistance.
[0049] Therefore, according to the present embodiment, it is possible to provide the polarizing plate 10 which is thin and highly flexible and has durability in a high-temperature and high-humidity environment.
[0050] The polarizing plate 10 of this embodiment can be used in combination with an image display panel such as a liquid crystal panel or an organic EL panel to form an image display device. The image display device can also have a touch panel. The polarizing plate 10 of this embodiment has both high flexibility and durability in a high temperature and high humidity environment, and can therefore be suitably used as an image display device disposed on a curved surface in a vehicle.
[0051] Example
[0052] Hereinafter, embodiments for implementing the present invention will be described.
[0053] A hard coat layer-forming composition was prepared containing a polymerizable material, a hydrophobic material, a photopolymerization initiator, and a solvent in the ratios shown in Table 1. The ratio of dihydrocyclopentanediethyl acrylate in the total solid content of the hard coat layer-forming composition was as follows.
[0054] Composition 1: 18%
[0055] Composition 2: 45%
[0056] Composition 3: 90%
[0057] Composition 4: 9%
[0058] · Composition 5: 0%
[0059] The prepared hard coat layer-forming composition was applied onto a 40 μm thick TAC film (trade name: TJ25 manufactured by FUJI FILM) using a wire bar coater so that the film thickness after curing would be the value described in Table 2. The film was dried by heating in an oven at 60° C. for 1 minute and then cured in a UV curing device in a nitrogen atmosphere (oxygen concentration of 500 ppm or less) at a cumulative light intensity of 100 mJ / cm 2 The coating film was cured by irradiating ultraviolet rays in a manner of 100 μm to prepare a protective film A (hard coating film). In addition, a COP film having a thickness of 26 μm was used as a protective film B.
[0060] [Table 1]
[0061]
[0062] The TAC film surface of the protective film A and the polarizer were bonded together using a water paste and dried, and then the protective film B was bonded to the polarizer using a UV curable adhesive. The UV curable adhesive was cured by irradiating with ultraviolet rays to obtain a polarizing plate.
[0063] (Moisture Permeability)
[0064] According to the moisture permeability test method (cup method) for moisture-proof packaging materials specified in JIS Z 0208:1976, the moisture permeabilities TA and TB of the protective film A and the protective film B before being attached to the polarizer were measured at 40°C and 90 RH%.
[0065] (Bending resistance)
[0066] The protective film A was cut into a sample of 3 cm x 10 cm in size and wound around an iron rod (mandrel) of a predetermined diameter with the hard coating layer facing the outside. The minimum diameter of the iron rod without surface cracks was used as the evaluation value of the bending resistance.
[0067] (Pencil hardness)
[0068] Using a pencil (uni, 3H manufactured by Mitsubishi Pencil Co., Ltd.) and a Clemens scratch tester (HA-301, manufactured by TESTERSANGYO Co., Ltd.), a scratch test was performed on the hard coat surface of the protective film A under the conditions of a load of 500 g and a scratch speed of 0.5 mm / sec. The scratch test was performed on 5 samples, and the samples with two or more scratches on the hard coat surface were evaluated as NG, and the other samples were evaluated as OK.
[0069] (Polarization Degree of Polarizing Plate after High-Temperature and High-Humidity Durability Test)
[0070] The polarizing plates involved in each embodiment and each comparative example were placed in a thermostatic chamber at 85°C and 85%RH, and the polarization degree was measured 240 hours and 500 hours after the placement. It should be noted that the polarization degree was calculated by correcting the value measured by an absorptiophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation) using a 2-degree viewing field (C light source) of JIS Z 8701 for visibility.
[0071] Table 2 shows the properties of the protective films A and B according to the examples and comparative examples and the measured values of the polarization degree of the polarizing plate (initial value, before and after the high-temperature and high-humidity durability test).
[0072] [Table 2]
[0073]
[0074] Since the moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B of the polarizing plates of Examples 1 to 7 satisfy the above conditions (1) and (2), even after being placed in a constant temperature bath at 85°C and 85% RH for 500 hours, they still show a high value of polarization. In addition, since the thickness of the protective film A is less than 50 μm, even when it is wound on a mandrel with a diameter of 2 mm, no cracks will occur on the surface of the hard coating, and the bending resistance is excellent. In addition, since the protective film A has a hard coating, the surface hardness is also better than that of Comparative Examples 12 and 13 in which a hard coating is not provided.
[0075] In contrast, in Comparative Example 1, since the thickness of the protective film A was 50 μm, cracks occurred on the surface of the hard coat layer when the protective film A was wound on a mandrel having a diameter of 2 mm, and the bending resistance of the protective film A was inferior to that of the examples.
[0076] The polarizing plate according to Comparative Example 2 could not sufficiently suppress the intrusion of moisture from the outside because the protective film A had a high moisture permeability TA, and the polarization degree after being placed in a thermostatic chamber at 85° C. and 85% RH for 500 hours was lower than that of the examples.
[0077] The polarizing plates involved in Comparative Examples 3 to 6 do not fully exhibit bending resistance because the hard coating layer of the protective film A has few structural units derived from the (meth)acrylate having an alicyclic structure, and the bending resistance of the protective film A is inferior to that of the examples. It should be noted that the protective film A of Comparative Example 2, in which the hard coating layer is formed from the same composition as that of Comparative Examples 3 to 6, exhibits the same bending resistance as that of the examples, which is believed to be because the layer thickness of the protective film A of Comparative Example 2 is relatively thin, which suppresses stress concentration on the surface of the hard coating layer.
[0078] The polarizing plates involved in Comparative Examples 7 to 9 cannot fully suppress the intrusion of moisture from the outside because the moisture permeability TA of the protective film A is high. Compared with the example, the polarization degree after being put into a constant temperature bath at 85°C and 85% RH for 500 hours is reduced. In addition, the polarizing plates involved in Comparative Examples 8 and 9 do not contain structural units from (meth)acrylates having an alicyclic structure in the hard coating layer of the protective film A, so they cannot fully exhibit bending resistance, and the bending resistance of the protective film A is worse than that of the example. It should be noted that the protective film A of Comparative Example 7, which forms a hard coating layer from the same composition as Comparative Examples 8 and 9, exhibits the same bending resistance as the example. It is believed that this is because the layer thickness of the protective film A of Comparative Example 7 is relatively thin, which suppresses stress concentration on the surface of the hard coating layer.
[0079] Since the polarizing plates according to Comparative Examples 10 and 11 did not contain a structural unit derived from (meth)acrylate having an alicyclic structure in the hard coat layer of the protective film A, they could not sufficiently exhibit bending resistance, and the bending resistance of the protective film A was inferior to that of the examples.
[0080] Compared with the examples, the polarization degree of the polarizing plates involved in Comparative Examples 12 and 13 decreased after being placed in a thermostatic chamber at 85°C and 85% RH for 500 hours. It is believed that this is because the moisture permeability TA of the protective film A is too low, so when exposed to high temperature and high humidity, the moisture contained in the protective film A and / or the adhesive (water paste) continues to remain in the polarizing plate, resulting in the deterioration of the polarizer. In addition, the protective film A of Comparative Examples 12 and 13 is not provided with a hard coating layer, so the surface hardness is worse than that of the examples.
[0081] Industrial Applicability
[0082] The present invention can be used as a polarizing plate used in a display device, and is particularly suitable as a polarizing plate for a display device used in a high temperature environment such as in a vehicle.
[0083] Explanation of symbols
[0084] 1 Polarizing filter
[0085] 2TAC film
[0086] 3Hard coating
[0087] 10 polarizing plates
[0088] AProtective FilmA
[0089] B Protective Film
Claims
1. A polarizing plate, wherein a protective film A is attached to one surface of a polarizer and a protective film B is attached to the other surface, characterized in that: The moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B at 40° C. and 90% RH simultaneously satisfy the following conditions (1) and (2), The protective film A has a hard coating layer composed of a cured film of a composition, wherein the composition contains a (meth)acrylate compound containing an alicyclic structure and a photopolymerization initiator, and the content ratio of the (meth)acrylate compound containing an alicyclic structure is 20% by mass or more of the total solid content. The thickness of the protective film A is less than 50 μm. 240g / m 2 / day>TA>70g / m 2 / day…(1) 70g / m 2 / day ≥ TB…(2).
2. The polarizing plate according to claim 1, wherein The protective film A is a hard coating film in which the hard coating layer is laminated on one surface of a triacetylcellulose film.
3. The polarizing plate according to claim 2, wherein: The hard coating film has a pencil hardness of 3H or more.
4. The polarizing plate according to claim 1, wherein The protective film B is a film made of any one of cycloolefin polymer, polyethylene terephthalate, and polymethyl methacrylate. 5 . A display device comprising the polarizing plate according to claim 1 .
Citation Information
Patent Citations
Polarizing plate and display device using the same
JP2021144076A
